Synthesis and biological activity of schiff based and ruthenium P-Cymene complexes containing ethynylpyridine bridged to quinazoline derivatives - Dilebo, Kabelo Bramley (My University, 2019)
Imidazolyl-ethanamine Schiff base ligands of the N^N type were prepared by condensation reaction of histamine dihydrochloride with para-substituted aldehyde derivatives to yield: (E)-N-benzylidene-2-(1H-imidazol-4-yl)ethanamine 119a, 4-((E)(2-(1H-imidazol-4-yl)ethylimino)methyl)phenol 119b, E)-N-(4-fluorobenzylidene)-2(1H-imidazol-4-yl)ethanamine 119c and (E)-N-(4-nitrobenzylidene)-2-(1H-imidazol-4yl)ethanamine 119d, which were characterised by 1H and 13C-NMR, FTIR specroscopy and HRMS. 2D-NMR experiments (1H-1H COSY and 2D-HMBC) for representative ligand 119b were performed to qualify success in the condensation reaction. An attempted reaction to coordinate Schiff base ligand 119c to zinc chloride was carried out in an NMR tube and traces of the product were observed between 12 and 24 h monitoring using 1H-NMR. Iodine promoted cyclocondensation reaction of anthranilamide and para-substituted aldehyde derivatives afforded 2-aryl-quinazolin4(3H)-ones 120a-e and subsequent chloro-aromatisation reaction in SOCl2 afforded electrophilic C4-(Cl) 2-aryl-4-chloro-quinazolines 121a-e and the compounds were characterised by 1H and 13C-NMR and FTIR spectroscopic techniques. The 2-aryl-4chloro-quinazolines served as prerequisites for de-chloro amination on the C4-(Cl) position by 2-amino-3-nitropyridine to yield 2-aryl-N-(3-nitropyridin-2-yl)quinazolin-4amine derivatives 123a-e in good yield and the derivatives were characterised by 1H and 13C-NMR, FTIR and HRMS spectroscopic techniques. The C4-(Cl) position further allowed for Sonogashira cross-coupling with ethynylpyridine to yield 2-aryl-4(ethynylpyridine)quinazoline derivatives 125a-e which were characterised by 1H and 13C-NMR, FTIR and HRMS spectroscopic techniques. The 2-aryl-4(ethynylpyridine)quinazoline served as ligands for coordination to monomeric pcymene ruthenium(ll) which yielded (ɳ6-p-cymene)RuCl2-2-aryl-4(ethynylpyridine)quinazoline derivatives 126a-e in good yield. Compounds 126a-e were characterised by 1H and 13C-NMR, FTIR and HRMS spectroscopic techniques. 2D-HMBC NMR of representative ligands 126c and 126e showed long range couplings from 1JCH to 9JCH and this was confirmed by coordination induced shifts (CIS) ranging from 1 ppm to 11 ppm. Compounds 119a-d, 123a-e and 125a-e were inductively docked into the active receptors of tyrosine kinase (PDB:2SRC), glutamine synthetase (PDB:1HTO) and oxidoreductase (PDB:3F8P). The docking scores obtained gave hits ranging from -5 to -10 Kcal/mol. Compounds 119a-d, 121a-e, 123a-e, 125a-e and 126a-e were assayed employing the broth-dilution method which gave promising anti-Mycobaterium tuberculosis activity. Compound 125e gave good activity of <0.244 µg/mL over 7 day and 14 day sampling. Coordination of ligands 125a-e to Ru(ll) group resulted in loss of activity, notably for ligand 125e.
Thesis(M.Sc. (Chemistry)) -- University of Limpopo, 2019
Keywords: Synthesis; Ethyntlpyridine; Ruthenium P-Cymene; Biosynthesis; Biochemistry